ANALISIS LITERATUR: PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR DI SEKOLAH DASAR - Marsha Dilla; Arifin Maksum; Anggit Aruwiyantoko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Improvement of student learning outcomes is the main indicator in determining whether an education that is implemented is of good quality or not. The low learning outcomes of students, especially in Elementary Schools, are influenced by one factor, namely the inappropriateness of the model applied by educators. Therefore, in order for student learning outcomes to improve, it is necessary to adjust the learning model based on student needs and educational environment conditions. Analysis of the use of the Student Teams Achievement Division cooperative learning model is very appropriate to analyze the improvement of student learning outcomes in Elementary Schools. This research is a research with a qualitative approach in which a literature study was conducted to analyze and present data that students' understanding of concepts, learning outcome, and social skills can increase due to the implementation of STAD. STAD is one of the learning methods that is very effective and relevant to the needs of Elementary School students today, so that it can support active and meaningful learning